Konsep Dasar Pengembangan Media dan Sumber Belajar untuk MI/SD - Lili Kurniasih; Mitta Pebri; Nursakinah Lubis (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
One of the effective learning methods is the development of media and learning resources. The use of interesting and appropriate media for children in MI/SD is very important because children tend to learn through visuals and audio. Learning resources and learning media are very important to increase student motivation, make learning easier to understand, and make learning active and fun. Using a literature study methodology, this study investigates the ideas, roles, and importance of media and learning resources in the learning process. The results show how important the role of teachers is in selecting and developing learning media, as well as how important it is to manage a learning resource center to ensure high-quality basic education.